2019
DOI: 10.1093/ofid/ofz384
|View full text |Cite|
|
Sign up to set email alerts
|

An Outbreak of Brucellosis: An Adult and Pediatric Case Series

Abstract: Background Brucellosis is recognized as a neglected zoonotic disease and a major public health threat. The purpose of this study was to characterize epidemiological risk factors and healthcare utilization and compare clinical aspects of disease among adult and pediatric cases in North Texas. Methods A retrospective chart review of electronic medical records was completed at 3 large tertiary centers—Parkland Health and Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
2
8
0
3
Order By: Relevance
“…7 In this study, complicated brucellosis was observed only in four cases supporting the information that focal disease complications were less frequent in children than adults. 10 Clinical response to preferred treatment regimen was consistent with a recent big meta-analysis. 11 Relapses occurred in 6.4% of followed-up cases at an average of 6 months after treatment.…”
Section: Discussionsupporting
confidence: 82%
“…7 In this study, complicated brucellosis was observed only in four cases supporting the information that focal disease complications were less frequent in children than adults. 10 Clinical response to preferred treatment regimen was consistent with a recent big meta-analysis. 11 Relapses occurred in 6.4% of followed-up cases at an average of 6 months after treatment.…”
Section: Discussionsupporting
confidence: 82%
“…En nuestros 39 casos confirmados las manifestaciones clínicas más frecuentes fueron bastante inespecíficas (fiebre, cefalea, astenia, adinamia/ artralgia/mialgia, náuseas, dolor abdominal y diaforesis). Sin embargo, no en todos los estudios se reportan estos síntomas en la misma proporción; por ejemplo, en un estudio realizado en China, los pacientes presentaron principalmente astenia (74%), hiperhidrosis (55%), dolor muscular y articular (59,5%); en nuestro estudio estas manifestaciones obtuvieron los porcentajes más bajos [24][25][26] . En un meta-análisis internacional, los adultos manifestaron astenia (81%), fiebre (73%), artralgia (65%), mialgia (56%), diaforesis (55%), dolor lumbar (49%) y escalofríos (47%).…”
Section: Discussionunclassified
“…refieren manifestaciones gastrointestinales como dolor abdominal/vómito/diarrea hasta en 50%, mientras que en nuestro estudio no pasan de 20% e incluso la diarrea no la presentó paciente alguno. La cefalea sí se presentó en cifras similares: EUA en 40% y México en 45,5%; la astenia, la adinamia y las artralgias se refieren en EUA con una mayor frecuencia que en nuestro estudio (40%); las artralgias en el meta-análisis internacional fueron de las manifestaciones principales con un 71% de frecuencia, sin embargo, la astenia y las mialgias sólo se presentaron en 24 y 18%, lo cual es similar a los resultados de nuestro estudio 13,25 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…On physical examination, ndings are hepatomegaly and splenomegaly, lymphadenopathy, osteoarticular manifestations, genitourinary complications, neurological ndings, mucocutaneous manifestations, and pulmonary manifestations. The disease is transmitted via consumption of unpasteurized dairy products, direct contact with infected animals, inhalation of contaminated aerosols, and rarely human-to-human transmission [3]. Although intrauterine transmission, transmission during delivery, and transmission through breast milk are indeed among the main routes of transmission in the mammalian reservoirs, limited data support vertical transmission of human brucellosis [4,5].…”
Section: Introductionmentioning
confidence: 99%